A SOCIOLOGICAL STUDY ON CHILD LABOUR: IN THE CONTEXT OF CHILDREN'S PSYCHOLOGY, HEALTH, EDUCATION AND FAMILY LIFE - Singh, Rajesh; Verma, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Child labour is a serious social abuse that affects the future of children, especially in developing countries. This study examines the effects of child labour on children's psychology, health, education and family life in the context of the shoe industry in Agra district. Child labour is extremely common in the shoe industry in Agra district, where they have to work under difficult and dangerous conditions. The study was conducted through primary data collection through interviews among local workers, industry owners and concerned officials. The results indicate that economic deprivation, lack of education and absence of social policies promote child labour. Also, the study highlights that child labour has a serious negative impact on the physical and mental development of children.